(untitled) (Colombia Medica, 2006)
Introduction: Low birth weight is a health problem in non-developed countries, with a neonatal mortality rate 35 times higher in Latin America than the expected one. At the neonatal care unit of the University Hospital in Cali, Colombia, 75% of all live newborn infants are < 2,500 g. Objectives: To evaluate the infants who were followed up until 40 weeks of postconceptional age in the kangaroo mother program. Methodology: A cohort study was performed in newborns infants < 2,001 g who were admitted to the neonatal unit of the Hospital Universitario del Valle, Cali, Colombia, if they had overcome all major adaption problems to extrauterine life and had a family willing to follow the instructions. Exclusion criteria were lethal or major malformations, early detected major conditions arising from perinatal problem (severe hypoxic-ischaemic encephalopaty, pulmonary hypertension and intracerebral hemorrage III or IV), and either abandoned children or those who were given for adoption. All patients were monitored in physical growth, length of breast-feeding, morbility, mortality, readmissions, hospital stay and bed turn. Measurement were made at discharge, at 40 weeks of postconceptional age. Results: A total of 66 infants reached term, 40 (61%) were girls and 26 (39%) were boys, with a mean birth gestational age of 32 weeks (27-38) and mean birth weight of 1,434 g (700-1,950). Infants were discharged with mean gestational age of 34 weeks (31-39), mean postconceptional age of 19 day (4-48) and mean weight of 1,552 g (1,359-2,239). During the following they had a mean weight-gain of 18 g/kg/day. A large proportion of infants received breast-feeding: 96% at discharge and 94% at term. Exclusive breast-feeding: 67% at discharge and 51% at term. Anemia and gastroesophageal reflux disease after discharge were the main causes of morbidity. Only three (4.5%) infants were readmissed before the 40 week, two for criotherapy and one for apnea, none died. The hospital stay at neonatal unit was 17.5 days and the bed turn was 1.37 patients/bed/month. Conclusions: Kangaroo mother program showed to be a safe alternative to the care of low birth weight infants, since it gives at least an early discharge, skin-to-skin contact and a good quality nutrition based initially on breast-feeding.